Horizontal and vertical food web structure drives trace element trophic transfer in Terra Nova Bay, Antarctica - Signa, Geraldina; Calizza, Edoardo; Costantini, Maria Letizia; Tramati, Cecilia; Sporta Caputi, Simona; Mazzola, Antonio; Rossi, Loreto; Vizzini, Salvatrice (Environmental Pollution, 2019)
Despite a vast amount of literature has focused on trace element (TE) contamination in Antarctica during the last decades, the assessment of the main pathways driving TE transfer to the biota is still an overlooked issue. This limits the ability to predict how variations in sea-ice dynamics and productivity due to climate change will affect TE allocation in the food web. Here, food web structure of Tethys Bay (Terra Nova Bay, Ross Sea, Antarctica) was first characterised by analysing carbon and nitrogen stable isotopes (δ13C, δ15N) in organic matter sources (sediment and planktonic, benthic and sympagic primary producers) and consumers (zooplankton, benthic invertebrates, fish and birds). Diet and trophic position were also characterised using Bayesian mixing models. Then, relationships between stable isotopes, diet and TEs (Cd, Cr, Co, Cu, Hg, Ni, Pb and V) were assessed in order to evaluate if and how horizontal (organic matter pathways) and vertical (trophic position) food web features influence TE transfer to the biota. Regressions between log[TE] and δ13C revealed that the sympagic pathway drives accumulation of V in primary consumers and Cd and Hg in secondary consumers, and that a coupled benthic/pelagic pathway drives Pb transfer to all consumers. Regressions between log[TE] and δ15N showed that only Hg biomagnifies across trophic levels, while all the others TEs showed a biodilution pattern, consistent with patterns observed in temperate food webs. Although the Cd behavior needs further investigations, the present findings provide new insights about the role of basal sources in the transfer of TEs in polar systems. This is especially important nowadays in light of the forecasted trophic changes potentially resulting from climate change-induced modification of sea-ice dynamics.